Evolución y ecología trófica de los cachalotes (Physeteroidea) del Cenozoico en la costa del Perú: una revisión - Fernando Del Águila Grondona; Daniel Barona (Bulletin de l'Institut Français d'Études Andines)
The complex evolutionary history of cetaceans is the result of a series of ‘turnovers’ events, adaptive radiations and a series of different morphological transformations. Such processes can be evidenced by the fossil findings, especially from the Chilcatay and Pisco formations, which has gained scientific importance due to the additions of newly found species. In this work, the scattered information is compiled, offering a complete vision of the evolutionary trajectory and a first approximation to the trophic ecology of fossil sperm whales (Physeteroidea) present in the Cenozoic on the coasts of Peru. Only the specimens identified to the species level will be considered. Sperm whales arose in the late Oligocene (28 to 23 million years ago), reaching maximum diversity in the Miocene, when the following nine species can be described: Rhaphicetus valenciae (Early Miocene and Late Miocene), Acrophyseter deinodon, Acrophyseter robustus, Livyathan melvillei, Kogia danomurai, Koristocetus pescei, Platyscaphokogia landinii, Scaphokogia cochlearis and Scaphokogia totajpe. They finally declined at the beginning of the Pliocene with a great reduction in their diversity and the disappearance of the macroraptorial role. The following findings and studies attempt to understand this decline in detail as well as the interspecific relationships in order to understand the dynamics of the Peruvian marine-coastal community during the Cenozoic.